Child Emotion Review Application Design with Design Thinking Empathizing Process - Hayoung Youn; Jihyun Kim; Na Ma; Jisun Lee; Shannen P. Widjaja; Hyoun K. Kim; Hyun-kyung Lee (한국디자인포럼, 2022)
Background In recent years, it has been found that there has been an increase in mental illnesses in children and infants in Korea. According to existing findings and our observation, detailed feedback on children's emotional expression is essential for their growth and emotional health. Thus, to contribute in combatting this ongoing problem, the purpose of this paper is to design an application that can help review and monitor the emotions of 5-6-year-old children in order to improve their emotion regulation. By focusing on children's emotion regulation theory and design thinking methods, we designed a mobile application prototype with features intended to help children express their feelings and provide feedback for them. Through children’s direct participation and feedbacks during user testing, we were able to observe and analyze how the features and functions affect children's emotional expression. Methods This research is based on a qualitative study using design thinking methods where the data were collected through interviews and usability tests were conducted to measure the performance of the application and user satisfaction. The interviews were conducted to understand the behavioral characteristics of children aged 5 to 6. The findings were then used to determine and design of the elements and features of the application. After developing a prototype, usability tests were conducted with 7 children from South Korea, China, and Indonesia. Through interviews and surveys, insight and feedback to optimize the application were discovered. Result It has been found through our observation that overall, children between the age of 5 and 6 were interested in using the emotion review application. The presented emojis, designed as a potato character, played an important role in attracting children's interest. Moreover, this application simply reviewed the children's emotions and helped the parents to have a better understanding of the children and to improve parent-child communication. Thus, we can conclude that this application is able to help express children's emotions, and through utilizing the application, a positive relationship between children and parents can be formed. Conclusion The process of leading 5-6 years children to openly express their emotions and share their emotions was difficult. However, we found that if the children are visually interested in the mobile devices that they are familiar with or if there is active assistance from their parents, the process can proceed smoothly. Therefore, by utilizing an interesting form of emotion monitoring system for children combined with parents’ participation and support, children‘s emotion development can be strengthened and therefore can help with emotion regulation and emotional health.